INTELLECTUAL CAPITAL DAN KINERJA KEUANGAN PERSPEKTIF CAMELS : STUDI EMPIRIS PADA PERBANKAN SYARIAH DI INDONESIA - Gita Puspita (FEB Universitas Sultan Ageng Tirtayasa, 2019)
This study aims to examine the influence of Intellectual Capital as measured by iB-VAIC (Islamic Banking VAIC) in sharia banking in Indonesia to financial performance as measured by CAMELS perspective. The population of this research is Sharia Banking located in Indonesia and already registered with Indonesian Banking and Indonesia Financial Services Authority (OJK). The research criteria from the sample data used in this research is the Sharia Commercial Bank in Indonesia from 2008 to 2016. The method of data collection in this research are documentation and observation on the annual report of Sharia Commercial Bank. The data processed by using SPSS program version 24.0 by doing simple linear regression approach. The results of this study indicate that iB-VAIC has a significant effect on CAR, NPM, ROA and ROE. However no significant effect on NPL, NIM, BOPO, FDR, IRR and IER.